Limbal epithelial stem cells in corneal surface reconstruction - Wang, Li; Wang, Bowen; Ouyang, Hong (Annals of Eye Science; Vol 3 (January 2018): Annals of Eye Science, 2018)
Cornea serves as the partial front barrier and major light reflection organ of the eye. The integrity of corneal surface is essential for ocular function. Injuries or congenital diseases could significantly destruct the homeostasis of the ocular surface, especially the microenvironment of limbal epithelial stem cells (LESCs), and will eventually cause dysfunction of corneal regeneration and diminish of LESCs. The loss of LESCs by different reasons are named limbal stem cell deficiency (LSCD), which is one of the leading cause of vision loss worldwide. To restore the corneal surface, LESC transplantation in the form of tissue or cell cultures is currently a viable and promising method to treat LSCD. In this review, we aim to introduce the characters and niche of LESCs, and discuss different aspects of its application in cornea surface reconstruction.